Managing the organizational conflict in the departments of sports and school activities according to the opinion of the physical education (Journal of the College of Basic Education, 2022)
The study aimed to build and apply a scale of organizational conflict for the directors of sports and school activity departments. And to identify the organizational conflict of directors of sports and school activities. The researcher used the descriptive approach by the survey method and the correlational relationships due to its relevance to the nature of the research problem. The research community was determined from (the supervisors of sports and school activities) in the directorates of education in Baghdad. technical supervisor. The main sample was divided into three samples based on the requirements of the study to be the exploratory sample (30) supervisors (technicians) distributed over (6) directorates by (5) supervisors from each directorate and by simple random method (lots). The construction sample included (113), and after completing the final distribution process the questionnaires and answering them, the researcher obtained (100) questionnaires that were returned to by a supervisor, as the researcher built the scale on them. The application sample amounted to (130) supervisors, as it consisted of an exploratory sampleand construction, using the comprehensive inventory method. The researcher built a scale of organizational conflict and applied it to the supervisors of the sports and school activities departments in the districts of Baghdad. In light of the results obtained by the researcher through survey and field experiment and the use of appropriate statistical methods in the description, the researcher concluded the following conclusions:-The settlement strategy is the strategy most used by the directors of the sports and school activity departments, followed by the cooperation strategy, where the directors of the sports and school activities use these two strategies to a high degree. The courtesy strategy came in third place, followed by the strategy of using competition. As for the avoidance strategy, it comes in the fifth and last rank.In light of the conclusions, the researcher recommended the following:Giving the opportunity to all creative and serious supervisors in their efforts in sports and school activities, regardless of their years of experience, job titles, or the size of their responsibilities, and enhancing their contribution to decision-making and their affiliation with their institutions, which supports the achievement of its goals.